Determination of immunisation status of children between 2-5 years of age who attending to teaching institute with concern to both national immunization schedule and optional vaccines - Hanshila, Vudaga; Khadeer, Shaik; Sumera, Syeda (International Journal of Contemporary Pediatrics, 2024)
Background: In order to know the causes for non-immunisation, search for societal reasons for primary immunisation along with evaluating coverage. Aim of this current study is to determine the immunisation status of children between 2-5 years of age who are attending teaching health care centre with concern to both National Immunisation Schedule and Optional vaccines. Methods: Study analysed the children's immunisation status, factors affecting their immunisation coverage, and reasons for partial or incomplete immunisation. The information was obtained from the parents using a questionnaire. Information such as socio-demographic variables, immunisation status, causes of their partial immunisation and lack of immunisation. The "vaccination card and the recall" approach was used to determine the recipient's immunisation status. Results: Study found that 70.4% of children had received all recommended vaccinations. Lack of information and ignorance are significant contributors to under-immunization. Other statistically significant contributing factors for the low immunisation coverage include female gender, rural background, low socioeconomic status, born at home, lower mother age, and being from a joint household. BCG vaccination coverage was higher than pentavalent vaccine coverage, probably because of multiple doses needed. Only 77% of kids received vitamin A solution. Conclusions: Paediatrician should mention the next vaccination date and dose at each appointment in order to lower the vaccination dropouts. Parents should be informed regarding the date of vaccination of their child through SMS message, calls, and social media groups.